Large‐amplitude GPS TEC variations associated with Pc5–6 magnetic field variations observed on the ground and at geosynchronous orbit. Issue 9 (4th September 2015) - Watson, Chris; Jayachandran, P. T.; Singer, Howard J.; Redmon, Robert J.; Danskin, Donald
Abstract Large‐amplitude variations in GPS total electron content (TEC) at Pc5–6 (<6.67 mHz) frequencies have been observed, using a high data rate Global Positioning System (GPS) receiver of the Canadian High Arctic Ionospheric Network. TEC variations with peak‐to‐peak amplitudes of 2–7 TEC units (1 TECU = 1016 el m−2) were observed over a 2.5 h period in the postnoon sector on 9 September 2011, during a period of high auroral activity within a moderate geomagnetic storm. TEC observations were from the Sanikiluaq, Nunavut (56.54°N, 280.77°E) GPS receiver located in the auroral region. Over this same time period, compressional Pc5–6 magnetic field variations were observed by the geosynchronous GOES 13 magnetometer and the ground‐based Sanikiluaq magnetometer. GOES 13 has a northern magnetic footprint in close proximity to Sanikiluaq. Cross‐correlation analysis indicates that magnetic field and TEC variations were possibly linked. No natural hazards or nuclear explosions capable of exciting TEC perturbations were reported on this day. Using a triangulation technique involving TEC measurements of multiple GPS satellites, the propagation velocity of TEC variations in the ionosphere was also calculated. This calculation revealed two distinct events: lower frequency ( 0.9 mHz) TEC variations that propagated westward, consistent with the westward propagation of compressional Pc5 waves observed by GOES 13 and 15 satellites, and higher‐frequency ( 3.3 mHz) TEC variations that propagated southward. This is the first report of variations in ionospheric TEC linked to satellite observations of Pc5–6 ULF waves.